Phase Stability and Site Preference of Tb-Fe-Co-V Compounds - Jing Sun; Jiang Shen; Ping Qian (The Scientific World Journal)
The effect of cobalt on the structural properties of intermetallic Tb3Fe27.4−xCoxV1.6 with Nd3(Fe,Ti)29 structure has been studied by using interatomic pair potentials obtained through the lattice inversion method. Calculated results show that the preferential occupation site of the V atom is found to be the 4i(Fe3) site, and Fe atoms are substituted for Co atoms with a strong preference for the 8j(Fe8) site. The calculated lattice constants coincide quite well with experimental values. The calculated crystal structure can recover after either an overall wide-range macrodeformation or atomic random motion, demonstrating that this system has the stable structure of Nd3(Fe,Ti)29. All these prove the effectiveness of interatomic pair potentials obtained through the lattice inversion method in the description of rare-earth materials.